Iptek Bagi Masyarakat (IbM) Kelompok Usaha Pembuat Rusip - Robert Napitupulu; Rodika Rodika (Politeknik Manufaktur Negeri Bangka Belitung, 2017)
Nabila Rusip is one of the IKM built Disperindag Pangkalpinang City which makes the traditional food of the people of Bangka became popular and famous. This success is inseparable from the role of Local Government of Pangkalpinang City which continues to encourage Nabila Rusip business with the provision of appropriate technology in 2015 in processing fish raw materials for the manufacture of rusip. However, at this time the machine can not be operated again due to operator error in using the tool. The purpose of science and technology for the community of the business group of the russians is to repair the fish pressing machine for the manufacture of rusip which was received by the partner from the Industry and Trade Office of Pangkalpinang City. The implementation method starts from inventorying problems, the process of repair and manufacture of machinery, assembly, testing and lastly provides a brief training on how to operate and maintain the correct machine. The results of this activity obtained the fish machine can be re-operated, productivity Nabila Rusip increase and the sale proceeds to increase.